Três ensaios sobre Economia da saúde - Tavares, Fernanda Braga (2019)
This thesis consists of three essays about health economics. The first essay sought to review the literature on public-private choice in health services and on the determinants of self-perceived health status. In the second essay, the determinants of the choice of the new Brazilian middle class, without health insurance, were analyzed by the services of private practices / private clinics, based on the database of the National Health Survey (PNS, 2013). In general, the results indicated the profile of such individuals: they belong to smaller families, have already been diagnosed with some chronic disease, are married, white, in addition to making such a choice the higher the level of education, the better the self-perception of the state health and better quality in relation to structure and medical care. In addition, the waiting time and duration of the consultation are important in determining this demand. Using the same database, the third essay verified the determinants of self-perceived health in the presence of heteroscedasticity. From the Ordinal Generalized Linear Model, it is suggested that the residual variability in self- perceived health differed by diagnosis of chronic disease, by cigarette use, access to health insurance, exposure to violence, according to age and condition occupation, in which the analysis of residual variances indicates that the greatest presence of heterogeneity is found among individuals who have already suffered violence, smoke and have already been diagnosed with a chronic disease, in relation to their opposites, respectively. Individuals who have access to health insurance are less heterogeneous than those who do not.